Divergent synthesis of oxindolylidene acetates and spirooxindolopyrrolidones from arynes - Pandya, Virat G.; Mhaske, Santosh B. (Organic Letters, 2018)
A novel process for the preparation of various (E)-oxindolylidene acetates using arynes and carbamoylpropiolates has been developed. The utility of this protocol is also further extended to the one-pot synthesis of complex spirooxindolopyrrolidones. This method provides a milder and transition-metal-free access to both of the target scaffolds in moderate to good yields.